(untitled) (Texas Journal of Engineering and Technology, 2023)
The article presents the synthesis of organosilicon compounds based on tetraethoxylan and industrial by-products, as well as the ratio of reactants, solvents and temperature to the reaction product. Hydrophobic compositions based on synthesized organosilicon polymers were also developed and tests of the building material - concrete - were carried out. As a result, it turned out that the water absorption of concrete is reduced by 40%.